2015
DOI: 10.1111/ecc.12422
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training improves fatigue and quality of life in previously sedentary breast cancer survivors: a randomised controlled trial

Abstract: The primary aim of this study was to evaluate the benefits of resistance training (RT) on quality of life (QOL) and fatigue in breast cancer survivors as an adjunct to usual care. We recruited 39 women who had survived breast cancer [mean age (y) 51.9 ± 8.8; time since diagnosis (m) 11.6 ± 13.2]. Primary outcomes were fatigue as assessed by the Functional Assessment of Chronic Illness Therapy - Fatigue (FACIT) scale and QOL as assessed by the Functional Assessment of Cancer Therapy - General (FACT-G) scale. AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
1
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(150 citation statements)
references
References 56 publications
3
133
1
13
Order By: Relevance
“…Hagstrom et al (2015) employed the traditional ACSM guidelines in breast cancer survivors (with 2 days a week of machine-based exercises: leg extension, machine bench press, back extension) for the first 8 weeks of the study. Participants then transitioned to free weight, barbell compound exercises (squat, deadlift, bench press, etc) for the second 8 weeks 23. It is understood that free weight exercises stimulate muscle tissue to a greater degree than machine-based exercises 96 97.…”
Section: Discussionmentioning
confidence: 99%
“…Hagstrom et al (2015) employed the traditional ACSM guidelines in breast cancer survivors (with 2 days a week of machine-based exercises: leg extension, machine bench press, back extension) for the first 8 weeks of the study. Participants then transitioned to free weight, barbell compound exercises (squat, deadlift, bench press, etc) for the second 8 weeks 23. It is understood that free weight exercises stimulate muscle tissue to a greater degree than machine-based exercises 96 97.…”
Section: Discussionmentioning
confidence: 99%
“…Primary findings from this trial relating to immunological outcomes, muscular strength, quality of life, and fatigue have been previously reported [14,17,18]. Outcome measures were collected at week 0 and 17.…”
Section: Subjectsmentioning
confidence: 98%
“…This study was a post hoc analysis examining the effect of RT on telomere length in this cohort of women. The recruitment of participants, eligibility, exclusion criteria, and randomisation are described elsewhere [14,17,18]. To participate in the initial study, participants must have had a history of histologically confirmed stage I to IIIA breast cancer with no evidence of recurrent disease; age 18-70 years; completed surgery, radiotherapy, and/or chemotherapy; and sedentary (<30 min of structured, continuous moderate-intensity exercise, three times per week, and no current resistance training).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study evaluated exercise in previously sedentary breast cancer survivors [65] while another tested resistance exercise in comparison to relaxation control, showing beneficial results [66]. Rehabilitation may also play a role [67].…”
Section: • • Physical Activitymentioning
confidence: 99%